2020
DOI: 10.1021/acs.iecr.0c01846
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Production of Vanillin over CeOx and ZrO2 Modified Biomass-Templated Titania

Abstract: Walnut shell residues have been used as a sacrificial template in the synthesis of TiO 2 -based materials via mechanochemical synthesis. To improve the photocatalytic efficiency of the synthesized titania nanomaterials, functionalization with ceria and zircona was also investigated. Samples were characterized using a multitechnique approach, including X-ray diffraction, X-ray photoelectron spectroscopy, UV−visible spectroscopy, and scanning electron microscopy. Synthesized materials were employed as catalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…Various other metal nanoparticles immobilized on a variety of carriers such as metal organic frameworks (MOFs), carbon, titania, and ceria have been also investigated. [59][60][61][62] Photocatalytic oxidations of vanillyl alcohol to vanillin over Ce and Zr oxide supported on biomass-templated titania were also reported by Muñoz-Batista and Luque et al 63 These smart materials showed excellent selectivity (99%) toward vanillin; however, the conversion of vanillyl alcohol was not great (maximum 52%). Similar photocatalytic conversion of vanillyl alcohol to vanillin under mild reaction conditions are reported by other groups.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Various other metal nanoparticles immobilized on a variety of carriers such as metal organic frameworks (MOFs), carbon, titania, and ceria have been also investigated. [59][60][61][62] Photocatalytic oxidations of vanillyl alcohol to vanillin over Ce and Zr oxide supported on biomass-templated titania were also reported by Muñoz-Batista and Luque et al 63 These smart materials showed excellent selectivity (99%) toward vanillin; however, the conversion of vanillyl alcohol was not great (maximum 52%). Similar photocatalytic conversion of vanillyl alcohol to vanillin under mild reaction conditions are reported by other groups.…”
Section: Introductionsupporting
confidence: 52%
“…Similarly, excellent selectivity could not be achieved using metal nanoparticles. [58][59][60][61][62] Although high selectivity could be achieved using photocatalysts, [63][64][65] poor conversion was a major issue in contrast to complete conversion achieved with the present catalyst. Hence, we can conclude that we have developed a significantly improved catalytic protocols as compared to the existing catalytic system for the aerobic oxidation of vanillyl alcohol to vanillin.…”
Section: Resultsmentioning
confidence: 99%
“…182.4 eV, while the distance between Zr 3d 5/2 y Zr 3d 3/2 bands were shown to be ca. 2.5 eV, indicating the formation of Zr (IV) species [30]. Additionally, Ni XPS region was acquired for the three Ni modified samples.…”
Section: Resultsmentioning
confidence: 99%
“…Several semiconductor heterojunction photocatalysts have been fabricated to achieve an excellent activity in catalysis and dye degradation, but only a few photocatalysts have been documented for the photocatalytic conversion of VOL to VAL, which are associated with low VOL conversion and selectivity of VAL. Various heterogeneous photocatalytic materials based on TiO 2 , NiFe 2 O 4 , ZnFe 2 O 4 , CeO 2 , and ZrO 2 and catalysts involving noble metals have been reported for VOL to VAL transformation, but there is still a need for methods associated with effective oxidation of HMF and VOL, with high product selectivity under mild photocatalytic reaction conditions, using a simple photocatalyst.…”
Section: Introductionmentioning
confidence: 99%